2019
DOI: 10.21037/jtd.2018.12.136
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of malignancy and survival in patients with idiopathic pleuritis

Abstract: Background: The long-term outcome after non-diagnostic thoracoscopy (idiopathic pleuritis) has not been investigated in nationwide studies, and the survival has never been estimated. Therefore, we decided to investigate the three-year incidence of malignancy and survival of patients with idiopathic pleuritis. Methods: Retrospective, register-based, nationwide study of patients undergoing diagnostic video-assisted thoracoscopic surgery (VATS) thoracoscopy ≤30 days after thoracentesis, using The National Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
1
8
2
2
Order By: Relevance
“…The malignancies diagnosed during follow-up were one mesothelioma, two gynaecological cancers, one primary renal cell cancer and one cancer of unknown primary tumour. So, in our study, there seems to be no specific primary cancer type that is missed frequently, in contradiction with the data of several other studies, in which frequently malignant mesothelioma or metastatic pulmonary carcinoma were diagnosed 9 14–16…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The malignancies diagnosed during follow-up were one mesothelioma, two gynaecological cancers, one primary renal cell cancer and one cancer of unknown primary tumour. So, in our study, there seems to be no specific primary cancer type that is missed frequently, in contradiction with the data of several other studies, in which frequently malignant mesothelioma or metastatic pulmonary carcinoma were diagnosed 9 14–16…”
Section: Discussioncontrasting
confidence: 99%
“…This is also comparable to two other studies, in which both 5% of malignancy was diagnosed during follow-up,14 15 however, in other studies up to 25% of malignancy was found,22 23 in the latter after a mean period of 6 months. In another study in a tertiary referral hospital with high incidence of mesothelioma 12% showed to have malignant pleural effusion, all of them mesothelioma related, and mean follow-up until diagnosis was 9.8 (±4.6) months 24.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Various datasets have described a finding of NSP following pleural biopsy, with a mean incidence of 40%, 95% CI (38 -41%). [2][3][4][5][6][7][8][9][10][11][12][13][14][15] The pathophysiological mechanisms underpinning NSP are poorly understood, and it may simply represent a final common inflammation or fibrotic pathway. There are no prospective databases on NSP, and all the evidence so far is based on single centre, retrospective studies.…”
Section: Introduction (2958/3000 Words)mentioning
confidence: 99%
“…Moreover, MPE can be mimicked by other common causes of exudative pleural effusion such as pleural tuberculosis (TB) and parapneumonic effusion [5]. Thus, there is an increasing need to discover non-invasive biomarkers to diagnose or rule-out MPE accurately and e ciently in clinical practice [6].…”
mentioning
confidence: 99%